Growth of Solutions of Higher Order Complex Linear Differential Equations in an Angular Domain of Unit Disc (Journal of Mathematical Study, 2015)
We study the growth of solutions of higher order complex differential equationsin an angular domain of the unit disc instead of the whole unit disc. Some conditionson coefficient functions, which will guarantee all non-trivial solutions of thehigher order differential equations have fast growing, are found in this paper.